BUSINESS ANALYSIS AGROINDUSTRY PANCAKE DURIAN (Case Study on Agro-Industry Enterprises Pondok Durian Pancake Fifa in Marpoyan Damai District, Pekanbaru City): ANALISIS USAHA AGROINDUSTRI PANCAKE DURIAN (Studi Kasus pada Usaha Agroindustri Pancake Durian Pondok Fifa Di Kecamatan Marpoyan Damai Kota Pekanbaru) - Vino Defira Putra (Jurnal Agribisnis, 2021)
This study aims to (1) Knowing the processing of durian pancakes in Marpoyan Damai District, (2) Analyzing production costs, income, and added value of the pancake agro-industry. durian in Marpoyan Damai District (3) Analyzing the efficiency of durian pancake agro-industry in Marpoyan Damai District. This research was conducted at Pondok Fifa durian pancake agro-industry in Marpoyan Damai District, Pekanbaru City. The results of the calculation of this study indicate that the total cost incurred in one month of production is Rp. 17,827,492, the income earned is Rp. 39,930,000, and the profit earned is Rp. 22,102,508 in one month of production. The value of R / C is more than 1, which is 2.23, this means that the durian pancake agro-industry is feasible to develop and get profit. The added value of durian pancakes is Rp. 610,000 / Kg. Keywords: agro-industry, income, business efficiency, added value